Bibliometric Analysis: Lecturers' Research Performance - Silalahi, Rudi Yanto Batara; Moeins, Anoesyirwan; Marhalinda (Program Studi S3 Ilmu Manajemen, 2024)
The research performance of lecturers is very important for several reasons, both in terms of the development of higher education institutions and the broader contributions to society and scientific knowledge. This study aims to identify research trends related to lecturers' research performance from 2019 to 2024. To achieve this goal, a literature review method was used, employing bibliometric analysis with VOSviewer software. In this study, the applied method is a quantitative approach using bibliometric analysis. As a data source, 644 scientific publications from the ScienceDirect database were used, selected through a search with the keyword